A novel approach to improve flexural strength of Al2O3‐20 wt% ZrO2 composites by oscillatory pressure sintering. Issue 4 (27th November 2017) - Zhu, Tianbin; Xie, Zhipeng; Han, Yao; Li, Shuang; Li, Yawei; An, Di; Luo, Xudong
Abstract: In this communication, Al2 O3 ‐20 wt% ZrO2 composites (ZTA) were prepared by a novel oscillatory pressure sintering (OPS) process. An almost perfectly full density of 99.94% and a relatively high flexural strength of 1145 MPa can be achieved for the OPS‐fabricated specimen, which were higher than those prepared by pressureless sintering (98.24% and 682 MPa) and hot pressing (99.53% and 990 MPa). The enhancement of flexural strength of the OPS‐fabricated specimen was correlated with its smaller flaw size and higher fracture surface energy. It was suggested that OPS was an effective approach to fabricate ZTA composites with ultrahigh density and high strength.